2006
DOI: 10.1124/jpet.105.098467
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Volume-Sensitive Osmolyte Efflux from Human SH-SY5Y Neuroblastoma Cells following Activation of Lysophospholipid Receptors

Abstract: The ability of the lysophospholipids sphingosine 1-phosphate (S1P) and lysophosphatidic acid (LPA) to promote the release of the organic osmolyte taurine in response to hypoosmotic stress has been examined. Incubation of SH-SY5Y neuroblastoma cells under hypoosmotic conditions (230 mOsM) resulted in a time-dependent release of taurine that was markedly enhanced (3-7-fold) by the addition of micromolar concentrations of either S1P or LPA. At optimal concentrations, the effects of S1P and LPA on taurine efflux w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
54
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(71 citation statements)
references
References 37 publications
15
54
2
Order By: Relevance
“…42) On the other hand, in response to hypotonic stress, osmolyte extrusion recovers cell volume, and studies in TR-iBRB2 cells suggests that the volume of the retinal capillary endothelial cells is regulated by volume-sensitive organic osmolyte and anion channel (VSOAC) that releases taurine in response to hypoosmotic stress. 41,43) Subsequently, studies under hypotonic conditions suggested the induction of taurine transport of the retinal capillary endothelial cells in the presence of sphingosine-1-phosphate (S1P), a ligand of G proteincoupled receptors (GPCRs), 41) and the induction of volumesensitive taurine release by retinal capillary endothelial cells through GPCRs is also consistent with a previous report on GPCRs associated with osmolarity regulation. 44) In the retina, nerve activity is constant, and the various types of neurotransmitters released cause osmolarity fluctuations in the retinal microenvironment, such as the retinal extracellular fluid (ECF).…”
Section: Role Of Taurine Transport In Cell Vol-ume Regulation In the supporting
confidence: 73%
“…42) On the other hand, in response to hypotonic stress, osmolyte extrusion recovers cell volume, and studies in TR-iBRB2 cells suggests that the volume of the retinal capillary endothelial cells is regulated by volume-sensitive organic osmolyte and anion channel (VSOAC) that releases taurine in response to hypoosmotic stress. 41,43) Subsequently, studies under hypotonic conditions suggested the induction of taurine transport of the retinal capillary endothelial cells in the presence of sphingosine-1-phosphate (S1P), a ligand of G proteincoupled receptors (GPCRs), 41) and the induction of volumesensitive taurine release by retinal capillary endothelial cells through GPCRs is also consistent with a previous report on GPCRs associated with osmolarity regulation. 44) In the retina, nerve activity is constant, and the various types of neurotransmitters released cause osmolarity fluctuations in the retinal microenvironment, such as the retinal extracellular fluid (ECF).…”
Section: Role Of Taurine Transport In Cell Vol-ume Regulation In the supporting
confidence: 73%
“…This is in agreement with a number of previous findings (Du and Sorota 1999;Falktoft and Lambert 2004;Mongin and Kimelberg 2005;Heacock et al 2006;Cheema et al 2007). Additional work is needed to establish if aforementioned PKC dependence of hypoosmotic VRAC activation in HeLa, HTC and Mz-ChA-1 cells (Roman et al 1998;Hermoso et al 2004) is restricted to a few cell types or is more universal phenomenon.…”
Section: Conventional Pkc Isoforms Are Major Contributors To Vrac Regsupporting
confidence: 83%
“…However, a number of laboratories have demonstrated that stimulation of GPCRs, including several metabotropic P2Y receptors for ATP and ADP, produces limited activation of a VRAC-like pathway in non-swollen cells and greatly increases its activity in cells exposed to hypoosmotic medium (Jeremic et al 2001;Mongin and Kimelberg 2002;Mongin and Kimelberg 2003;Loveday et al 2003;Darby et al 2003;Franco et al 2004). Depending on the experimental system and the GPCR involved, PKCs have been found to play major or minor roles in the regulation of VRAC activity by GPCR agonists (Loveday et al 2003;Falktoft and Lambert 2004;Mongin and Kimelberg 2005;Heacock et al 2006;Cheema et al 2007;Ramos-Mandujano et al 2007). In HeLa cells, HTC rat hepatoma cells, and Mz-ChA-1 human cholangiocarcinoma cells, PKC activity was found to be critical for hypotonic (i.e.…”
Section: Conventional Pkc Isoforms Are Major Contributors To Vrac Regmentioning
confidence: 99%
See 1 more Smart Citation
“…In C 6 glioma cells, activation of several phosphoinositide-linked receptors has previously been demonstrated to facilitate D-aspartate uptake (Najimi et al, 2002(Najimi et al, , 2005Fournier et al, 2004). In this context, it may be relevant that of the GPCRs tested in SH-SY5Y neuroblastoma only the mAChR couples to phosphoinositide hydrolysis in this cell line (Heacock et al, 2006). D-Aspartate uptake into SH-SY5Y cells was mediated via a high-affinity, NaCl-dependent, saturable transport system that could be blocked by L␀BA, a potent inhibitor of the neuron-specific glutamate transporter EAAT3.…”
Section: Discussionmentioning
confidence: 99%